Disassembling lexical bundles clustered within rhetorical moves in discussion sections of qualitative and quantitative articles: a comparative analysis - Mohammed, Mohammed S.; Abdul Jabar, Mohd A.; A. Halim, Hazlina; M. Kasim, Zalina (Society of Cultural Studies and Social Sciences, 2023)
Producing academic research papers stands as a paramount undertaking for researchers seeking to disseminate their expertise and establish their presence within their respective disciplinary communities. Exploring the linguistic attributes embedded within the rhetorical structures of academic research papers aids in enhancing our comprehension of this frequently employed genre. Consequently, the principal aim of this investigation was to scrutinize the functional elements of lexical bundles clustered within the rhetorical moves in the Discussion sections of specialized corpora containing qualitative and quantitative research articles (RAs) within the domain of Applied Linguistics. Each corpus encompassed a total of 50 Discussion sections. The data underwent analysis based on the methodology outlined by Ruiying and Allison (2003) for discerning rhetorical moves. A corpus-driven methodology was employed to identify four-word lexical bundles and the functional taxonomy introduced by Salazar (2014) was employed to dissect these bundles. The scrutiny of the Discussion sections brought to light variations in the frequency of lexical bundles, highlighting those certain moves exhibited a greater prevalence of bundles compared to others. Notably, both qualitative and quantitative article authors demonstrated a similar pattern of preference, favouring text-oriented bundles over functional bundle categories in the Discussion sections. This study has contributed to a deeper understanding of lexical bundles and genre conventions within both qualitative and quantitative research papers, thereby equipping authors, especially those in the early stages of their academic journey, with enhanced knowledge and skills essential for proficient academic writing.